The Influence Of Service Quality On Consumer Satisfaction At Public Fuel Filling Station 7493701 PT Buton Bumi Mega Kilometer 4 Baubau City - Rifki Dayanti Ananda,; Asmiddin, Asmiddin; Andi Tenri (Sean Institute, 2024)
This study aims to determine the effect of service quality on consumer satisfaction at the 7493701 PT. Buton Bumi Mega Kilometer 4 public fuel station in Baubau City. This study is a quantitative survey study with a survey method. The design of this study begins with determining the research problem, collecting research data, and analyzing data. Data collected through questionnaires, all existing data are then analyzed quantitatively to see how much influence the service has on consumer satisfaction at the 7493701 PT Buton Bumi Mega Kilometer 4 public fuel station in Baubau City. The results of this study indicate that the results of simple regression testing state that service quality has an effect on consumer satisfaction at the PT Buton Bumi Mega Km 4 gas station in Baubau City. While partial testing of service quality has a positive and significant effect on consumer satisfaction. The coefficient of determination value shows the amount of contribution given to the service quality variable to the consumer satisfaction variable at the PT Buton Bumi Mega Kilometer 4 gas station in Baubau City.